Plane waves at an interface of thermoelastic and magneto-thermoelastic media - Rani, Annu; Madan, Dinesh Kumar; Kumar, Naveen; Punia, Mukesh (Mathematical Modelling and Analysis, 2024)
This research examines the propagation of waves in a semi-infinite, isotropic magneto-thermoelastic solid, and a semi-infinite thermoelastic solid with welded contact. The study investigates the influence of a magnetic field on amplitude coefficients for the incidence of thermal, SV, and P waves in the magnetothermoelastic solid in a semi-infinite space. The incidence of these waves results in a total of six waves, including both refracted and reflected waves. The fluctuation of amplitude coefficients for various magnetic pressure values is explored for copper and aluminum as numerical constants. The study observes that the amplitude coefficients of seismic waves, occurring during the incidence of thermal, SV, and P waves in the magneto-thermoelastic solid semi-infinite space, are dependent on the incident angle, magnetic field, and material constants. Notably, the amplitude coefficients for the incidence of SV waves exhibit only a minor influence from the magnetic field. The implications of this research extend to applications in ocean acoustics, geophysics, acoustic devices, composite materials, and non-destructive testing.